Otimização e validação de métodos analíticos para a determinação simultânea de tuberculostáticos (4-FDC) por CLAE/DAD e CLUE/ DAD - Paiva, Marcelo Vitor de (2013)
Tuberculosis is a serious disease, but curable in practically 100% of new cases, since complied the principles of modern chemotherapy. Isoniazid (ISN), Rifampicin (RIF), Pyrazinamide (PYR) and Chloride Ethambutol (ETA) are considered first line drugs in the treatment of tuberculosis, by combining the highest level of efficiency with acceptable degree of toxicity. Concerning USP 33 - NF28 (2010) the chromatography analysis to 3 of 4 drugs (ISN, PYR and RIF) last in average 15 minutes and 10 minutes more to obtain the 4th drug (ETA) using a column and mobile phase mixture different, becoming its industrial application unfavorable. Thus, many studies have being carried out to minimize this problem. An alternative would use the UFLC, which is based with the same principles of HPLC, however it uses stationary phases with particles smaller than 2 μm. Therefore, this study goals to develop and validate new analytical methods to determine simultaneously the drugs by HPLC/DAD and UFLC/DAD. For this, a analytical screening was carried out, which verified that is necessary a gradient of mobile phase system A (acetate buffer:methanol 94:6 v/v) and B (acetate buffer:acetonitrile 55:45 v/v). Furthermore, to the development and optimization of the method in HPLC and UFLC, with achievement of the values of system suitability into the criteria limits required for both techniques, the validations have began. Standard solutions and tablets test solutions were prepared and injected into HPLC and UFLC, containing 0.008 mg/mL ISN, 0.043 mg/mL PYR, 0.030 mg.mL-1 ETA and 0.016 mg/mL RIF. The validation of analytical methods for HPLC and UFLC was carried out with the determination of specificity/selectivity, analytical curve, linearity, precision, limits of detection and quantification, accuracy and robustness. The methods were adequate for determination of 4 drugs separately without interfered with the others. Precise, due to the fact of the methods demonstrated since with the days variation, besides the repeatability, the values were into the level required by the regular agency. Linear (R> 0,99), once the methods were capable to demonstrate results directly proportional to the concentration of the analyte sample, within of specified range. Accurate, once the methods were capable to present values of variation coefficient and recovery percentage into the required limits (98 to 102%). The methods showed LOD and LOQ very low showing the high sensitivity of the methods for the four drugs. The robustness of the methods were evaluate, facing the temperature and flow changes, where they showed robustness just with the preview conditions established of temperature and flow, abrupt changes may influence with the results of methods